ETNOSENTRISME DALAM NOVEL CIUMAN DI BAWAH HUJAN KARYA LAN FANG: SEBUAH PERBANDINGAN - Helmi, M. (Jurnal Sastra Aksara, 2018)
Literary works are perceived through elements of form and content. In addition, the comparative element also deepens the understanding of literary works. This is so applied to the novel Ciuman di Bawah Hujan (kiss under rainfall) by Lan Fang. This work is discussed through three main issues: structural elements, content elements, and comparative elements. With descriptive approach, data collection is done by documentation method and technique of text study through structuralism, semiotics, and comparative study. The analysis was done by descriptive method, structural-base method and content analysis technique. Based on the discussion, this novel presents an interesting structure by presenting the story in the story. The plot of this model is similar to a cerita berbingkai (framed story). In the novel sense the meaning of this novel is interesting to bring the figure and its relation to the title of rain. From this aspect of the novel comparison, it shows that ethnocentrism in various cultures in Indonesia is still quite relevant.